How Intrinsic Motivation, Work Discipline, and Organizational Citizenship Behavior Affect Employee Performance - Maretha Audina; Rini Handayani - (Enrichment : Journal of Management, 2021)
This study aims to determine the effect of intrinsic motivation, work discipline, and organizational citizenship behavior on the performance of employees of the BPJS Health in Purwodadi, Grobogan Regency. The sampling technique used a saturated sampling technique with a sample size of 79 employees. The results showed that intrinsic motivation and work discipline had a significant effect on the performance of BPJS Health employees in Purwodadi, Grobogan Regency. However, Organizational Citizenship Behavior has no effect on employee performance. Through the F test, it is known that the variables of intrinsic motivation, work discipline, and organizational citizenship behavior simultaneously affect the performance of BPJS Health employees in Purwodadi, Grobogan Regency. Meanwhile, the Adjusted R square value of 0.724 shows the influence of intrinsic motivation, work discipline, and Organizational Citizenship Behavior variables together on employee performance variables is 72.4% and the remaining 27.6% is influenced by other variables outside the proposed research model.